Jumlah Bintil Fase Vegetatif Penentu Mutu dan Hasil Kacang Hijau (Vigna radiata L.) di Lahan Sawah Bekas Padi - Triana Sari; Taryono Taryono (Agrotechnology Innovation (Agrinova), 2021)
Mungbean is one of leguminosae, that has profitable prospect therefore it has been cultivated by Indonesian society. Mungbean showed early maturity, easy management during cultivation and can produce more biomass, about 11.00-12.00 t/ ha. Wwhen the crop residue is left in field, it benefits of increasing the nutrients and improving soil fertility. Such reason makes mungbean becomes more profitable than soybean and peanut. The mungbean genetic   material is significant to develop superior mungbean and support sustainable agriculture. This research was conducted to study the presence of rhizobium after continues rice grwon fields, to determine the bean accession responsive to Rhizobium sp., and to determine the impact of Rhizobium sp. on the mungbean yields components. This research was conducted at Agrotechnology Innovation Centre of Universitas Gadjah Mada (PIAT UGM) Kalitirto, Berbah, Sleman, Yogyakarta in splitted completely randomized design (CRD) with two factors. The main factor is inoculation treatment and the sub-factor is 18 mung beans accessions. Observations included rhizobium infection, nodule components, fresh weight of plant, dry weight of plant and yield components. The data obtained was further analyzed using analysis variance of completely randomized design, a further test of Scott Knott, and correlation analysis. All accessions can be infected by rhizobium and there was an increase in number of nodules and the effective number of nodules in each observation time with the result that inoculation treatment was superior to the one without inoculation. Number of nodules at time of observations have positive corellation with yield component, increased number of nodules followed increased variable of yield component.